Characteristics of a Continuous Direct Foaming Technique. (27th January 2015) - Luthardt, Fabian; Adler, Jörg; Michaelis, Alexander
Abstract : Continuous direct foaming techniques for ceramics promise economical and ecological advantages compared to other manufacturing routes. No additional template is needed to generate a foam structure, and no fugitive pore formers have to be burned out. Using only air as the pore former, much lower emissions of waste gases can be achieved during the heat treatment of the foam. The challenge of the direct foaming technique is the control of the metastable wet foam state where foam destabilization processes can change or destroy the foam structure. Complex rheological and microscopic measurements were developed to investigate the relationship between rheological parameters and foam stability. It could be shown that the storage modulus G' is the dominant factor describing the stability of the wet foam. The shear‐thinning behavior and the value of the viscosity of the slurry define the possible foam porosity in dependence of the manufacturing parameters of the foaming device. Foamability and foam stability are rheological contrary to each other. The Sauter diameter D32 was used to characterize the pore size. Theoretical calculations of the Sauter diameter D32 could be verified by experimental data. Suitable parameters are shown to produce stable foams with high porosities.